A practice based approach to forest governance - Arts, Bas; Behagel, Jelle; Turnhout, Esther; de Koning, Jessica; van Bommel, Séverine (Forest policy and economics, 2014)
‘Forest governance’ refers to new modes of regulation in the forest sector, such as decentralized, community-based and market-oriented policy instruments and management approaches. Its main theoretical basis consists of two mainstream models: rational choice and neo-institutionalism. Since these models rest upon problematic conceptualisations of ‘the social’, this paper proposes a so-called ‘practice based approach’, which offers a comprehensive understanding of social dynamics related to trees, forests and biodiversity. It tries to go beyond some of the old dualisms in social theory, such as subject and object, human and nature and agency and structure. Three sensitising concepts – situated agency, logic of practice and performativity – are introduced and their application is illustrated by a number of examples from forest governance practices: joint forest management in India, decentralized forest management in Bolivia and the construction of biodiversity datasets in Europe. The paper also addresses some of the criticisms the approach has received.